The Effect of Arbuscular Vesicular Mycorrhizae on the Efficiency of Phosphate Absorption on the Growth and Production of Cayenne Pepper (Capsicum Frutescens L. ) - Muhammad Abror; Mustofa Mauludin (Universitas Muhammadiyah Sidoarjo, 2015)
This study aims to determine the effect of vesicular arbuscular mycorrhiza and phosphate fertilization on the growth and production of cayenne pepper (Capsicum frutescens L. ). Research conducted at the Greenhouse o f Faculty of Agriculture, University of Muhammadiyah Sidoarjo. Factorial experiment arranged in a completely randomized design (CRD) with repeat 4 times. The first factor: VA mycorrhizal (with and without mycorrhiza); the second factor: phosphate (0, 100, 200 and 300 kg TSP/Ha). The variables measured were plant height, number of leaves, stem diameter, number of flowers, fruit number, fruit weight, fresh weight of plants, phosphate uptake. Data were analyzed by ANOVA followed by Duncan test 5%. Mycorrhizal fungi and phosphate give significantly different interaction effects on plant height, stem diameter, plant fresh weight, and phosphate uptake of plants with mycorrhizal fungi combination VA and phosphate 300 kg/Ha which gives the highest yield. Mycorrhizal fungi significant effect in increasing plant height, number of leaves, stem diameter, number of flowers, number of fruits, fruit weight and wet weight of plants and plant phosphate uptake. Phosphate significant effect in increasing plant height, number of leaves, stem diameter, number of flowers, number of fruits, fruit weight and wet weight of plants and plant phosphate uptake. There is no difference between the effect of phosphate 100 kgTSP/Ha with 200 and 300 kg/Ha TSP in high regard detainees, number of leaves, stem diameter, number of relationship, the amount of fruit, fruit weight, and plant fresh weight.